Tributação da folha de salários para financiar a previdência social no Brasil: um caso de persistência institucional - Vasconcelos, Breno Ferreira Martins (2024)
This thesis emerges from a challenging context regarding the Social Security in Brazil: despite Brazil having a high tax burden on payroll, both in absolute terms and in comparison with other countries, to fund Social Security, this revenue has been insufficient for covering expenses for years. Moreover, there is a growing risk of depletion of this incidence base due to changes in the labor market and the aging population. Nevertheless, this remains a persistent public policy in the Brazilian tax system, pratically unchanged since 1935. The central argument of this thesis, grounded in neoinstitutionalist doctrine, is that the combination of incentives generated across institutional domains contributes to the persistence of this public policy. The institutional domains identified in the work are: the granting of tax benefits, the formation of a thriving tax litigation market, the concentration of resources collected from social security contributions in the federal government, the configuration of an indirect and opaque taxation system, leading to the phenomenon of fiscal illusion, and the conceptual rigidity of labor and social security norms regarding possible categories of employment relationships. These five domains interrelate through institutional complementarities, exposed within a context of rationality in economic action. In conclusion, we aim to demonstrate this comprehensive framework of institutions that generate individually advantageous but collectively suboptimal incentives, mutually reinforcing and ensuring the institutional persistence of high payroll taxation in Brazil.